The Effect of Peer Interaction on Students' Learning Outcomes in a Digital Environment Mediated with Computer Self-Efficacy - Ilmi, Hanifah Mufidatul; Ranu, Meylia Elizabeth (MANAZHIM, 2025)
This study was conducted in response to inconsistent findings in previous research regarding the impact of peer interaction on student learning outcomes. It aims to examine the effect of peer interaction on learning outcomes within a digital learning environment, with computer self-efficacy serving as a mediating variable. Utilizing a causal-associative design and a quantitative approach, the study employed purposive sampling to select 248 student participants. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results revealed that: (1) peer interaction has a significant and positive effect on learning outcomes; (2) peer interaction significantly and positively influences computer self-efficacy; (3) computer self-efficacy has a significant but negative effect on learning outcomes; and (4) the indirect effect analysis indicates that peer interaction significantly and negatively influences learning outcomes when mediated by computer self-efficacy. These findings underscore the importance of fostering supportive peer environments to enhance students’ confidence in digital tool usage and to optimize learning outcomes.